2013
DOI: 10.1111/jfb.12109
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization and in vivo image analysis of novel zebrafish Danio rerio pigment mutants

Abstract: This study reports the isolation and characterization of a new type of transparent zebrafish Danio rerio mutant called pinky (pk), which has been visually isolated from a spontaneous mutation in a D. rerio colony. The pk larvae possess complex mutations affecting pigmentation because of missing pigment cells or a dramatic reduction in the chromatophore number. The pk displays a totally colourless phenotype and adult body transplant with no other obvious external morphological abnormalities, except for a red re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…We also demonstrated that the function of hps1 is evolutionally conserved in vertebrates and accordingly established a fish model of HPS. Although previous studies have reported that hps1 knockdown in zebrafish causes a severe renal phenotype with pericardial effusion, yolk sac edema, and protein loss ( Schenk et al 2019 ), and have described pinky zebrafish mutant lacking pigmentation with mutations in some genes including hps1 ( Hsu et al 2013 ), our study is the first to report a genetic model fish without hps1 function. In addition, we showed that hps1 specifically affects the production of melanophores rather than other pigments ( Fig.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…We also demonstrated that the function of hps1 is evolutionally conserved in vertebrates and accordingly established a fish model of HPS. Although previous studies have reported that hps1 knockdown in zebrafish causes a severe renal phenotype with pericardial effusion, yolk sac edema, and protein loss ( Schenk et al 2019 ), and have described pinky zebrafish mutant lacking pigmentation with mutations in some genes including hps1 ( Hsu et al 2013 ), our study is the first to report a genetic model fish without hps1 function. In addition, we showed that hps1 specifically affects the production of melanophores rather than other pigments ( Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Although the genes were not identified, the zebrafish fade-out mutant has both ocular and blood clotting defects ( Bahadori et al 2006 ). In addition, the pinky zebrafish mutant has a loss of pigmentation and mutations in hps1 , ap3m2 , and rabggta ( Hsu et al 2013 ). The knockdown of hps genes in zebrafish has been reported to induce some HPS phenotypes, including renal protein loss ( Schenk et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%